PENGARUH KEMANDIRIAN BELAJAR DAN KECERDASAN EMOSIONAL DITINJAU DARI KEMAMPUAN PEMECAHAN MASALAH - Priarti Megawanti; Aji Nurdiansyah; Muhamad Farhan (CV Putra Publisher, 2022)
This study aims to determine: (1) the effect of learning independence and emotional intelligence on problem solving abilities, (2) the effect of independent learning on problem solving abilities, (3) the effect of emotional intelligence on problem solving abilities. This research is a survey research because it does not provide treatment, but only reveals facts that occur naturally and are already ongoing. The research subjects were 74 grade VIII SMP YAPIDA students in the 2019/2020 school year. The data was collected using a questionnaire or questionnaire method. Questionnaire or questionnaire method to collect data on Independent Learning, Emotional Intelligence, and Problem Solving. The sampling technique in this study was simple random sampling. In this study, 54% of the total population was taken as a sample in class VIII SMP Yapida as many as 40 students, while the sample for the instrument test was 34 samples. The results of independent learning and emotional intelligence on problem solving have a probability value of 0.002 < (0.05). So it can be concluded that there is a positive relationship between emotional intelligence and students' ability to solve mathematical problems. The results of independent learning on problem solving abilities show a significance value of Tcount 2.04 > 2.022 T table (significance level 5%) so that the conclusion is